Colonial origins, institutions and economic performance in the Caribbean : Guyana and Barbados - DaCosta, Michael (IMF [Washington]US, 2007)
Explores some of the origins of the divergence in economic performance and social indicators in Guyana and Barbados. Focuses on the deep seated factors that derive from the countries' history, geography and demographics.